A major practicum report at Nenita Quality Foods Corporation, Marapangi, Toril, Davao City - Mabano, Love Joy Cortez (2008)
The 288-hour plant practice at Nenita Quality Foods Corporation was conducted from April to May 2007 as part of the curriculum for the Bachelor of Science in Food Technology of UP Mindanao. The plant practice aimed to expose the student to actual plant operations, which include some hands-on activities on the company?s three main departments namely: fresh meat, production and quality assurance. Through the plant practice, the student acquired some information about the company including its profile, product lines, production and processing systems, and the good manufacturing practices it observes. This manuscript aims to show a detailed report of the information gathered from the plant practice, the student?s technical analyses on some production systems, and present some recommendations that may of help for the company?s improvement
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2008
Keywords: Good manufacturing practices; Nenita Quality Foods Corporation; Meats